EFFECT OF PROBLEM BASED LEARNING TO CRITICAL THINGKING SKILLS ELEMENTARY SCHOOL STUDENTS IN SOCIAL STUDIES - Rizki Pebriana; Disman Disman (PrimaryEdu : Journal of Primary Education, 2017)
The main problem of this study is the lack of ability to think kriis Elementary School fifth grade students in the learning of Social Sciences. This study uses a quantitative approach with quasi-experimental methods. The study population was the fifth-grade elementary school students in District Ciparay Bandung regency. The sample consisted of 51 students divided into 25 students in the class IV-A as an experimental group and 26 students in the class IV-B as the control group. Instruments used comprises a written test regarding social issues. Quantitative analysis is performed against the average pretest and post test critical thinking skills by using the t-test and Mann Whitney test. The results showed that the differences are critical thinking skills in students using problem-based learning model at initial measurement (pre-test) and the final measurement (post-test). encourage the student can solve his problems with critical thinking, there are no differences in the ability of critical thinking in students who use conventional learning model at initial measurement (pre-test) and the final measurement (post-test), there is an increased critical thinking skill in students whose learning using model-based the problem is higher than students whose learning using conventional learning.